Effects of the COVID-19 Pandemic and to Develop Strategies for Resistance on the Farming Practices in Ganjam District-An Analysis - Suchismita Sahu; Santosh Kumar Rout; Ankit Kumar Jena (Archives of Current Research International, 2024)
The present study entitled “Scientific study on the farming practices in ganjam district to comprehend the effects of the COVID-19 pandemic and to develop strategies for resistance” was undertaken with a view to evaluate COVID-19’s effects on farmers of Ganjam District of Odisha and to suggest them how to overcome such pandemic situation. The study followed purposive and random sampling techniques that were found appropriate and taken to undergo the analysis. The study was conducted in the Department of Agricultural Extension and Communication, Institute of Agricultural Sciences (IAS), Siksha ‘O’ Anusandhan University Bhubaneswar, between December 2020 and August 2022. For the selection of District, Blocks and Villages covering 120 respondents, information was collected through structured interview schedule and focus group discussion. Suitable tools and techniques used during the analysis to suffice the study need are frequency, percentage, mean score, standard deviation, Person’s coefficient Correlation, T- test, multiple regression was employed for analyzing collected data. The study revealed that majority of the respondents (85%) belong to middle and older group, having the sex ratio of 3:2 male and female. The study revealed that the education of children adversely affected with mean score of 2.625, further it has been observed that the farmers couldn’t ensure expenses on purchase of household materials. The study depicted that quality food consumption, expenditure habit and farming in general have been adversely affected. The banking activities as regard to getting loan, taking banking transactions have also been adversely affected. Several farmers have faced physical, socio-economic, technological and production constraints. In this study, particularly problem in sound sleep, depression, feeling of insecurity, slowdown of supply chain and non-availability of quality inputs for cultivation are the main focus constraints encountered by agriculture. It was also found that to mitigate such situation farmers had opined that the vaccine should be taken regularly and farmer should develop the saving habit for future use.